1997
DOI: 10.1086/304341
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Properties of Cygnus X‐1 during the Spectral Transitions

Abstract: We report the results from our timing analysis of 15 Rossi X-Ray T iming Explorer observations of Cygnus X-1 throughout its 1996 spectral transitions. The entire period can be divided into three distinct phases : (1) transition from the hard state to the soft state, (2) soft state, and (3) transition from the soft state back to the hard state. The observed X-ray properties (both temporal and spectral) in Phases 1 and 3 are remarkably similar, suggesting that the same physical processes are likely involved in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
207
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(253 citation statements)
references
References 30 publications
46
207
0
Order By: Relevance
“…In the spirit of the approach chosen here that avoids depending on models for the variability, we label the lower frequency variability component as component 1 and the higher frequency variability component as component 2. Both components shift to higher frequencies as Γ 1 softens (see also Cui et al 1997;Gilfanov et al 1999;Pottschmidt et al 2003;Axelsson et al 2005;Shaposhnikov & Titarchuk 2006;Böck et al 2011). The two components appear to have roughly similar strengths.…”
Section: Energy-independent Evolution Of Psds With Spectral Shapementioning
confidence: 87%
See 2 more Smart Citations
“…In the spirit of the approach chosen here that avoids depending on models for the variability, we label the lower frequency variability component as component 1 and the higher frequency variability component as component 2. Both components shift to higher frequencies as Γ 1 softens (see also Cui et al 1997;Gilfanov et al 1999;Pottschmidt et al 2003;Axelsson et al 2005;Shaposhnikov & Titarchuk 2006;Böck et al 2011). The two components appear to have roughly similar strengths.…”
Section: Energy-independent Evolution Of Psds With Spectral Shapementioning
confidence: 87%
“…The frequency shift of the variability components of the PSDs in the RXTE range with the softening of the source in the hard and intermediate states continues at higher energies (Cui et al 1997;Pottschmidt et al 2006;Cabanac et al 2011) up to ∼200 keV (Torii et al 2011), even though such high energy analyses are rare. The different energy dependence of the components has been previously noted for individual observations, both for the presented energy range and above (Cui et al 1997;Nowak et al 1999a;Pottschmidt et al 2006;Böck et al 2011), but never shown for such a comprehensive data set as presented in this work.…”
Section: Discussion Of Psd Shapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uttley et al (2002) applied this method to the first 3 years of observations of four AGN. They found evidence for bends, or breaks, in the PSDs in three AGN,NGC 5506,although not in NGC 5548. GBHs are found in a variety of 'states' (eg McClintock and Remillard 2003;Cui et al 1997a), the most common of which are the so called low flux, hard spectrum (or 'low') state, and the high flux, soft spectrum (or 'high') state. In the standard Comptonisation models for the production of X-ray emission, different physical regimes apply to low and high states, with a higher seed photon flux in the high state, leading to a cooler Comptonising corona (eg Zdziarski et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While an optically thick corona could precess with the accretion disc providing it had some nonuniform geometry, it is generally accepted that the corona is optically thin (e.g. Cui et al 1997). In this case the corona would not precess with the disc unless it was a very thin layer just above and below the disc, and therefore the BATSE modulation should be comparable with that of ASM.…”
Section: Discussionmentioning
confidence: 99%